1998
DOI: 10.1159/000020825
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Twin-Twin Transfusion Syndrome by Laser and Digoxin

Abstract: Objectives: A combination of surgical and medical approaches may address both the underlying pathophysiological processes and the most threatening symptoms in twin-twin transfusion syndrome (TTTS). Case: A primigravida with monochorionic twin pregnancy was referred with signs of TTTS at 16 weeks. One twin was severely hydropic with normal amniotic fluid, the co-twin had anhydramnios. Laser treatment was performed. Nevertheless, signs of severe cardiac decompensation in the recipient remained unchanged. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Jaeggi and co-workers in 1998 and Fouron in 2000 commenced the new era in prenatal SVT treatment based on the selection of the medicine depending on the type of arrhythmias 21,22 . In this review we analyzed the reports focusing on singleton pregnancies, but DeLia and Arabin published about digoxin in twin transfusion syndrome as an addition to laser resulting in foetal improvement 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaeggi and co-workers in 1998 and Fouron in 2000 commenced the new era in prenatal SVT treatment based on the selection of the medicine depending on the type of arrhythmias 21,22 . In this review we analyzed the reports focusing on singleton pregnancies, but DeLia and Arabin published about digoxin in twin transfusion syndrome as an addition to laser resulting in foetal improvement 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Digoxin treatment in cases other than SVT was applied in such abnormalities as: in foetuses with Ebstein's anomaly, critical AS , absent pulmonary valve syndrome, complete heart block, in foetuses with aneurysm/diverticulum of left ventricle, in tricuspid atresia or dysplasia, rhabdomyoma, pulmonary atresia, HLHS with fibroelastosis, in twin twin transfusion syndrome and in extracardiac anomalies such as atriovenous malformation or sacrococcygeal teratoma 4,5,6,8,9,10,11,23,24,37,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Doppler velocimetry of the ductus venosus in the recipient showed a loss of the D wave before laser treatment and an extreme reverse A-wave in the inferior vena cava, both as a sign of the high preload (Figure 8a, b), and the fiow velocity wave form of the ductus venosus of the donor sbowed a nearly normal pattern signifying a normal afterload (Figure 8c). After laser therapy, we additionally treated the cardiomegaly with transplacental digoxin [38] and the cardiac circumferences became equal with normal venous Doppler velocimetry after 6 weeks. The outcome of the twins bom at 37 weeks was uneventful.…”
Section: Tzvin-to-twin Transfusion Syndrome (Ttts)mentioning
confidence: 99%
“…Roman et al (1995) successfully treated hydropic recipients by using amniocentesis and digoxin. Arabin et al (1998) reported that cardiac decompensation and hydrops were reversible following combined surgical (laser) and medical (digoxin) approaches in a case with congestive heart failure 507 Twin Research Volume 5 Number 6 pp. 507-514…”
Section: Conservative Managementmentioning
confidence: 99%